The impact of discourse marker instruction on writing improvement of Iranian intermediate EFL learners / Ghader Asadzadian - Ghader, Asadzadian (2017)
The purpose of this study was to determine the plausible impact of discourse marker (DM) instruction on its usage, and also on fluency, accuracy, and complexity improvement of Iranian intermediate EFL learners’ writing. To this aim, among the two hundred fourth year English major learners in Dezful University, Iran, fifty of them who were in the intermediate level, based on the scoring system of the university, were chosen. They were divided into the experimental and control groups. The experimental group experienced a twenty-hour intervention period on function and usage of DMs through a process of explicit instruction (EI) and input flood (IF), during which they received direct corrective feedback (CF). The DM classification presented by Belles-Furtuno (2004), with some modifications to match the purpose of the current study, was selected to be taught to this group, including both micro and macro markers which can be applied in both sentential and supra-sentential levels. After intervention, both experimental and control groups were given a topic to write to elucidate if DM instruction could influence the use of these units. The results revealed that the experimental group used DMs more than the control group which means EI and IF, along with CF could have a positive impact on the use of these units. The next stage of the study was investigating the possible effect of EI and IF, with the help of CF, of DMs on fluency, accuracy, and complexity of writing. The experimental group was given topics prior to and following the intervention. To quantify the results the Wolfe-Quintero (1998) method was used. The data show that all the three components of writing improved after intervention, which suggest that DM instruction could enhance learners' writing in the three aspects. The findings can be used by teachers and syllabus designers to consider DM as one of the most crucial components in writing courses.